The importance of basic life support in the pediatric age group - Marinho, Nayara Priscila Resende; Verdan, Roberta Baldez; Fernandes, Alexandre Galvão (Seven Editora, 2023)
Cardiorespiratory Arrest (CRP) is defined by the sudden interruption of ventricular mechanical activity and breathing. In adults, CRP often has a cardiac etiology. However, in children, CRP is usually secondary to respiratory failure and shock. Despite advances, CRP in the pediatric age group is still associated with high lethality and neurological disorders. In order to reduce mortality and poor prognosis in children, it is essential to recognize an early stop and already start the Basic Life Support (BLS) that has particularities in relation to the age group, such as infant, child and adolescent. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-039